Gene Expression in Oligodendroglial Tumors. (2010) - Shaw, Elisabeth J.; Haylock, Brian; Husband, David; du Plessis, Daniel; Sibson, D. Ross; Warnke, Peter C.; Walker, Carol
Abstract : Background : Oligodendroglial tumors with 1p/19q loss are more likely to be chemosensitive and have longer survival than those with intact 1p/19q, but not all respond to chemotherapy, warranting investigation of the biological basis of chemosensitivity. Methods : Gene expression profiling was performed using amplified antisense RNA from 28 oligodendroglial tumors treated with chemotherapy (26 serial stereotactic biopsy, 2 resection). Expression of differentially expressed genes was validated by real-time PCR. Results : Unsupervised hierarchical clustering showed clustering of multiple samples from the same case in 14/17 cases and identified subgroups associated with tumor grade and 1p/19q status. 176 genes were differentially expressed, 164 being associated with 1p/19q loss (86% not on 1p or 19q). 94 genes differed between responders and non-responders to chemotherapy; 12 were not associated with 1p/19q loss. Significant differential expression was confirmed in 11/13 selected genes. Novel genes associated with response to therapy included SSBP2, GFRA1, FAP and RASD1 . IQGAP1, INA, TGIF1, NR2F2 and MYCBP were differentially expressed in oligodendroglial tumors with 1p/19q loss. Conclusion : Gene expression profiling using serial stereotactic biopsies indicated greater homogeneity within tumors than between tumors. Genes associated with 1p/19q status or response were identified warranting further elucidation of their role in oligodendroglial tumors.